Combining wide-field super-resolution microscopy and electron tomography: rendering nanoscopic correlative arrays on subcellular architecture - Braet, Filip; Cheng, Delfine; Huynh, Minh; Henriquez, Jeffrey; Shami, Gerry; Lampe, Marko (Correlative light and electron microscopy II, 2014)
In this chapter, the authors outline in full detail, an uncomplicated approach that enables the combination of wide-field fluorescence super-resolution microscopy with electron tomography, thereby providing an approach that affords the best possible confidence in the structures investigated. The methodical steps to obtain these high-throughput correlative nanoscopic arrays will be visually explored and outlined in detail. The authors will demonstrate the feasibility of the method on cultured Caco-2 colorectal cancer cells that are labeled for filamentous actin. The presented images, morphometric data, and generated models illustrate the strengths of our correlative approach for future advanced structural-biology-oriented questions. Correlative nanoscopy applications can be readily found in which there is a need to reveal biomolecular information at unprecedented resolution on subcellular behavior in various biological and pathobiological processes.
Gesehen am 12.11.2020